2004
DOI: 10.1161/01.hyp.0000128242.41442.71
|View full text |Cite
|
Sign up to set email alerts
|

Geneticism of Essential Hypertension

Abstract: T he idea that a person's genetic constitution is allimportant and that genetic knowledge is sufficiently advanced so that we can make judgments on our past or future health was called geneticism by Medawar. 1 He termed geneticism as the application to the human condition of a genetic knowledge or understanding that is assumed to be very much greater than it really is. Proponents of geneticism have promised us that the sequencing of the human genome will offer limitless insights into the pathogenesis of essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Several investigators have issued several nongenetic factors as predictors of hypertension status, like obesity, smoking habits, nutritional habits, physical activity and psychological status. [1][2][3][4][5][6][7] The results from our analysis remained similar, after controlling for several of the aforementioned factors, which enhance the eligibility of our reports.…”
Section: Demonstrated That Insupporting
confidence: 70%
See 1 more Smart Citation
“…Several investigators have issued several nongenetic factors as predictors of hypertension status, like obesity, smoking habits, nutritional habits, physical activity and psychological status. [1][2][3][4][5][6][7] The results from our analysis remained similar, after controlling for several of the aforementioned factors, which enhance the eligibility of our reports.…”
Section: Demonstrated That Insupporting
confidence: 70%
“…1 Polymorphisms in many genes have been implicated for predisposition to hypertension. [2][3][4] Siffert et al 4 first demonstrated a positive relationship between the polymorphism C825T in the GNB3 gene encoding the b3-subunit of heterotrimeric G proteins, with increased levels of blood pressure. However, there are other studies that have failed to show significant results regarding the relationship between the polymorphism C825T in the GNB3 gene and blood pressure levels.…”
mentioning
confidence: 99%
“…On the basis of previous arguments and potential functional polymorphisms, [1][2][3][4][5][6][7][8][9][10][11] we hypothesized that genetic polymorphisms in RAS genes, including AGT A-6G, A-20C, G-217A and T174 M, AT1R A1166C and ACE I/D, was associated with the occurrence of EH. The genotype, allele and haplotype frequencies were compared between the hypertensive and normotensive individuals, in an effort to explore the association between the six SNPs of RAS genes and EH in the population of Southern China.…”
Section: Firstmentioning
confidence: 99%
“…1 High blood pressure (BP) often leads to a series of pathologies, such as insulin resistance, abnormal metabolism of blood glucose and lipids as well as increased risks of various cerebrovascular and cardiovascular diseases, all of which are detrimental to human health condition. Although the precise aetiology of EH remains unclear, accumulating evidence has suggested that genetic susceptibility is an important factor for the development of EH.…”
Section: Introductionmentioning
confidence: 99%
“…Essential hypertension (EH), which is characterized by sustained elevated blood pressure (BP) with no identifiable cause, is a public health burden in the worldwide (1) and a complex polygenic disease determined by both genetic and environmental factors (2). A body of evidence suggests that the SELE gene plays an important role in the development and progression of hypertension.…”
Section: Introductionmentioning
confidence: 99%